Feeding management of ruminant animals to reduce their contribution for gas emission - Samsudin, Anjas Asmara @ Ab Hadi (UB Press, 2016)
It is estimated that the global human population is going to expand from 7.4 – 9.2 billion by the year 2050. This situation is definitely going to increase the demand for animal food products worldwide which will directly have an undesirable impact on the environment. Enteric methane from rumen methanogens and nitrous oxide from agricultural activities is estimated to be around 10-12% of the world‘s total anthropogenic greenhouse gas (GHG) emission. It is also estimated to increase by 30% above current levels by the year 2050. Reducing GHG emissions from ruminant livestock is a technically challenging even if the livestock production is constant. For methane mitigation strategies to be successful, it is important to establish which factors influence the rumen methanogen community and rumen volatile fatty acids (VFA) since this could reduce animal feed efficiency if it is not properly manage.